Ketidakpastian Hukum Pengaturan Naming Rights pada Fasilitas Publik yang Berstatus Cagar Budaya dalam Perspektif Hukum Positif di Indonesia - Hana Aurelia; Dwita Tarisa Putri; Zahra Aurrelia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The practice of naming rights through trademark licensing agreements on public facilities has become a common commercialisation strategy in Indonesia. However, when the object of naming rights is a public facility with cultural heritage status, legal uncertainty arises due to the absence of specific regulations governing the intersection between Law No. 20 of 2016 concerning Trademarks and Geographical Indications and Law No. 11 of 2010 concerning Cultural Heritage. The objective of this study is to analyse the regulation of naming rights on public facilities with cultural heritage status and to identify any differences in the application of trademark law in the cases of Semarang Tawang Station and Cirebon Kejaksan Station. The study employs a normative juridical method, utilising secondary data collection techniques and is supported by tertiary legal materials, employing a legislative, analytical and comparative approach. The results of the study indicate a discrepancy in the regulatory framework for naming rights concerning cultural heritage, leading to legal ambiguity due to inconsistent implementation. This is exemplified by the contrasting outcomes at Semarang Tawang Station, where the naming rights agreement with Bank Jateng was successfully executed, and at Cirebon Kejaksan Station, where the agreement was terminated despite both stations possessing cultural heritage status. The study recommends the introduction of comprehensive special regulations to harmonise the protection of exclusive trademark rights with the preservation of the identity and historical value of cultural heritage sites.